Enhancing tensile strength of Mg–Al–Ca wrought alloys by increasing Ca concentration. (July 2020) - Huang, Qiuyan; Liu, Yang; Tong, Min; Pan, Hucheng; Yang, Changlin; Luo, Tianjiao; Yang, Yuansheng
Abstract: The tensile strengths of the as-extruded Mg–Al–Ca ternary alloys at both ambient and elevated temperatures are enhanced via adding a high content of Ca element up to 6 wt%. High-temperature strength of the present rare-earth-free Mg alloys can be even compared with those of the reported Mg-RE alloys. The as-extruded Mg–6Al–6Ca (wt. %, AX66) alloy exhibits a tensile yield strength (YS) of 404 MPa and an ultimate tensile strength (UTS) of 415 MPa at room temperature, and YS of 225 MPa and UTS of 265 MPa at 200 °C, respectively. For the AX66 alloy, the nucleation rates of dynamic recrystallized (DRXed) grains are larger than those of the AX62 and AX64 alloys due to the typical particle stimulated nucleation effect. A number of long-rod Al2 Ca phase is dispersed at the grain boundaries of AX66 alloy, and a restricted degree of DRX is induced. Consequently, the majority ofα-Mg matrix exists in the as-deformed state involving a high density of subgrains. The combined effects of grain refinement hardening, texture hardening and precipitation hardening guarantee the high strength. Specially, numerous micron-scale bulk (Mg, Al)2 Ca phases are found to distribute among matrix, which play a critical role in maintaining the high thermal-resistance. Highlights: With the increasing the Ca content, strengths of Mg–Al–Ca alloys at both room temperature and 200 °C gradually increase. In the AX66 alloy with highest amount of Ca content, the nucleation rate of DRXed grains is large due to the typical PSN effect. A restricted degree of DRX would be induced in the AX66 alloy due to the formations of profuse nano-Al2 Ca phases. The high amounts of micron-scale bulk (Mg, Al)2 Ca phases should play the critical role in maintaining the high thermal resistance.